Good governance role for the relationship between road infrastructure development quality of life population in the municipality of Viqueque - Soares, Osvaldo; Muni, Joao; Vong, Manuel (PT. Publikasiku Academic Solution, 2025)
Road infrastructure development is crucial for improving community mobility, accessibility to services, and economic growth in rural areas like Viqueque, Timor-Leste. Good governance principles such as transparency, participation, and accountability play a vital role in achieving these goals. This research aims to explore the relationship between good governance and road infrastructure development and its impact on the quality of life in Viqueque. A qualitative descriptive design was used, employing purposive sampling to select key informants, including local officials, community leaders, and residents. Data was collected through interviews, observations, and documentation, and analyzed using content analysis. The study found that good governance significantly improves infrastructure quality and community welfare. However, lack of transparency, insufficient community participation, and budget constraints remain major challenges. For sustainable development, community involvement, improved governance, and adequate planning are necessary to ensure inclusive growth and enhanced living standards for the people of Viqueque.